Determination of the enantiomeric composition of chiral delta-2-thiazolines-1, 3 by 1H and 19F NMR spectroscopy using chiral solvating agents. Issue 3 (2006) - Merelli Merelli, Bérangère Bérangère; Menguy Menguy, Laurence Laurence; Soubeyrand-Lenoir Soubeyrand-Lenoir, Estelle Estelle; Cherton Cherton, Jean-Claude Jean-Claude
Abstract : Studies of the perturbing effect of chiral solvating agents (CSAs) namely the fluoroalcohols5a and5b upon the NMR spectra of chiral Δ 2 -thiazolines1 presenting interesting insecticidal properties demonstrated the ability of these CSAs to afford diastereomeric solvates from these substrates providing their enantiomeric discrimination. Thus, for five of the six tested Δ 2 -thiazolines1A and1B there is at least one possibility to proceed to their enantiomeric discrimination either by 1 H or 19 F NMR using mostly5b as CSA.